1992
DOI: 10.1128/mcb.12.4.1846
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta 1-responsive element: closely associated binding sites for USF and CCAAT-binding transcription factor-nuclear factor I in the type 1 plasminogen activator inhibitor gene.

Abstract: Transforming growth factor 13 (TGF-3) is the name of a group of closely related polypeptides characterized by a multiplicity of effects, including regulation of extracellular proteolysis and turnover of the extracellular matrix. Its cellular mechanism of action is largely unknown. TGF-131 is a strong and fast inducer of type 1 plasminogen activator inhibitor gene transcription. We have identified a TGF-131-responsive element in the 5'-flanking region of the human type 1 plasminogen activator inhibitor gene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
77
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 27 publications
5
77
0
Order By: Relevance
“…Examples for this are the insulin-mediated transcriptional activation of the fatty acid synthase gene (Wang & Sul 1995), and the glucose response of L-pyruvate kinase and Spot 14 transcription, which are both mediated by USF (Vallet et al 1997). USF is also involved in the contractile-induced expression of the cardiac a-myosin heavy chain (Ojamaa et al 1995), the injury-induced osteopontin expression of smooth muscle cells (Malyankar et al 1999), the TGF-b1 mediated induction of the human type 1 plasminogen inhibitor gene (Riccio et al 1992) and the induction of the metallthionein-I gene in response to H 2 O 2 and cadmium (Li et al 1998). H 2 O 2 and cadmium can induce oxidative stress, and the involvement of USF in oxidative stress could be related to the fact that USF can be functionally regulated in a redox-dependent manner (Pognonec et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Examples for this are the insulin-mediated transcriptional activation of the fatty acid synthase gene (Wang & Sul 1995), and the glucose response of L-pyruvate kinase and Spot 14 transcription, which are both mediated by USF (Vallet et al 1997). USF is also involved in the contractile-induced expression of the cardiac a-myosin heavy chain (Ojamaa et al 1995), the injury-induced osteopontin expression of smooth muscle cells (Malyankar et al 1999), the TGF-b1 mediated induction of the human type 1 plasminogen inhibitor gene (Riccio et al 1992) and the induction of the metallthionein-I gene in response to H 2 O 2 and cadmium (Li et al 1998). H 2 O 2 and cadmium can induce oxidative stress, and the involvement of USF in oxidative stress could be related to the fact that USF can be functionally regulated in a redox-dependent manner (Pognonec et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated this point by showing that retinoic acid (42), dexamethasone (15), and a serotonergic agonist 3 all can repress CT/CGRP gene expression through the CT/CGRP HLH-OB2 enhancer. The possibility that USF activity can be regulated has been suggested by Riccio et al (32), who have shown that transforming growth factor-␤ can regulate gene expression through overlapping USF-CTF/NF-I sites in the type 1 plasminogen activator inhibitor gene (32). Mutations in either the USF or CTF/NF-1 sites reduced transcriptional activation upon exposure to transforming growth factor-␤.…”
Section: Activity Of the Ct/cgrp Enhancer In The Context Of Flanking mentioning
confidence: 94%
“…For example, the insulin gene has been proposed to be controlled by the combinatorial actions of E47 HLH proteins and cell-specific homeodomain proteins (22,23). The USF HLH proteins have also been shown to functionally interact with other DNA binding proteins to activate transcription, including in a cell-specific manner (32,33,38). In the case of the CT/CGRP enhancer, we propose that cell specificity is provided by the OB2 protein.…”
Section: Activity Of the Ct/cgrp Enhancer In The Context Of Flanking mentioning
confidence: 99%
“…The precise mechanisms by which PPAR-g ligands modulate PAI-1 and uPA transcription remain to be defined. The PAI-1 promoter, which lacks a consensus PPAR response element (PPRE), contains cis-acting elements for CAAT/enhancer-binding protein and signal transducers and activators of transcription (35,36). It is conceivable that activation of PPAR-g induces the expression of other transcription factors, which in turn regulate PAI-1 gene transcription (37,38).…”
Section: Discussionmentioning
confidence: 99%